Assessment of Systemic Immune-Inflammatory (SII) Index, Systemic Inflammatory Response (SIR) Index, Neutrophil to HDL-C ratio (NHR), Monocyte to HDL-C ratio (MHR) and Lymphocyte to HDL-C ratio (LHR) as markers of Inflammation in Type 2 Diabetes Mellitus - Kiran N, Asha; K. Sravani, K. Sravani; A.Sirish, A.Sirish; N. Ramakrishna, N. Ramakrishna; Kumar, E. Kiran (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus (DM), a chronic metabolic disease with increasing prevalence in India. Type 2 diabetes mellitus (T2DM) and its associated vascular complications are major contributors to mortality and morbidity worldwide. Inflammation and immune response play a significant role in the pathogenic mechanism and progression of DM. Chronic low-grade inflammation contributes to organ dysfunction and tissue damage, promoting insulin resistance (IR) by inhibiting β-cell function, impairing insulin secretion, and accelerating apoptosis. Aim: The present study aimed to assess the systemic immune inflammation (SII) index and systemic inflammation response (SIR) Index in patients with T2DM. Materials and Methods: This retrospective study was conducted in the Department of Biochemistry in association with the Department of Pathology, Gayatri Vidhya Parishad Institute of Health Care & Medical Technology (GVPIHC&MT), Visakhapatnam, Andhra Pradesh, India. After obtaining the Institutional Ethics Committee, a total 280 subject’s data was collected. Among them, 140 were type 2 diabetes mellitus patients and 140 were non-diabetic subjects. Necessary details were collected from medical records including demographic details like age, sex, BMI and blood pressure. Details of biochemical parameters such as fasting and post-prandial glucose, urea, creatinine, total cholesterol, Triglycerides, and high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C) and HbA1c. Hematological parameters like complete blood count (CBC) values were collected. The SII index, SIR index, NHR, MHR and LHR were calculated by using the formulas. Results: In the present study, significant increase in blood pressure [(systolic 120.2±6.2 mmHg), (diastolic 80.2±2.2 mmHg)], fasting blood sugar (FBS) (155.2±50.1 mg/dl), post-prandial blood sugar (PPBS) (211.5±58.4 mg/dl), HbA1c (8.1±2.5 %), urea (30.4±7.1 mg/dl), creatinine (1.2±0.2 mg/dl), total cholesterol (196.7±56.7 mg/dl), triglycerides (178.5±68.5 mg/dl), LDL-C (130.6±31.5 mg/dl), VLDL-C (35.6±13.7 mg/dl) and neutrophil count (64.6±11.4 %) was observed in T2DM cases than non-diabetic subjects. Significant decrease in HDL-C (30.5±11.5 mg/dl), and lymphocytes (26.5±10.9%) observed in T2DM subjects. Concerned with inflammatory markers such as SII index (12.6±3.6), SIR index (25.7±5.2), NHR (1.9±0.72), MHR (0.15±0.08), PHR (0.07±0.02), NLR (4.2±1.1) and PLR (0.17±0.01) were significantly increased in T2DM cases than non-diabetic subjects. In this study, FBS significantly correlated (positive) with SII index (r=0.367), SIR index (r=0.199), NHR (r=0.524), MHR (r=0.368), PHR (r=0.225), and NLR (r=0.289). HbA1c also showed a positive correlation with SII index (r=0.253), SIR index (r=0.199), NHR (r=0.462), and PHR (r=0.198). Conclusion: The present study results may conclude significant elevation of inflammatory markers such as SII index, SIR index, NHR, MHR, PHR, NLR, and PLR and a significant positive correlation with blood sugar and HbA1c.